Polymer Adhesin Domains in Gram-Positive Cell Surface Proteins - Järvå, Michael A.; Hirt, Helmut; Dunny, Gary M.; Berntsson, Ronnie P.-A. (Frontiers in Microbiology, 2020)
Surface proteins in Gram-positive bacteria are often involved in biofilm formation, host-cell interactions and surface attachment. Here we review a protein module found in surface proteins that are often encoded on various mobile genetic elements like conjugative plasmids. This module binds to different types of polymers like DNA, lipoteichoic acid and glucans, and is here termed polymer adhesin domain. We analyse all proteins that contain a polymer adhesin domain and classify the proteins into distinct classes based on phylogenetic and protein domain analysis. Protein function and ligand binding show class specificity, information that will be useful in determining the function of the large number of so far uncharacterised proteins containing a polymer adhesin domain.